The Problem of the Relation of Hate and Enmity Under Article 282 Through the Prism of Publicity and Media - Yuliy Evgenievna Puhir (Сибирское юридическое обозрение, 2011)
The distinction and relation of concepts of «hatred» and of «hostility». The problematic issues of qualification incite hatred or enmity are considered.